Optimising translational oncology in clinical practice: Strategies to accelerate progress in drug development. Issue 2 (February 2015) - Stahel, R.; Bogaerts, J.; Ciardiello, F.; de Ruysscher, D.; Dubsky, P.; Ducreux, M.; Finn, S.; Laurent-Puig, P.; Peters, S.; Piccart, M.; Smit, E.; Sotiriou, C.; et al.
Highlights Treatment advances in oncology are limited and new approaches are needed. Tumour heterogeneity is a key issue underlying this lack of progress. Molecular characterisation of cancer subtypes could transform future treatment. Clinical trial recruitment for rare cancer subtypes is challenging. Potential collaborative approaches designed to accelerate progress are discussed.